Presence of Salmonella spp. on beef carcasses and meat contact surfaces at local abattoirs in Selangor, Malaysia - Chong, Elizabeth Sinirisan; Noraziah Mohamad Zin; Nur Faizah Abu Bakar; Siti Shahara Zulfakar (Penerbit Universiti Kebangsaan Malaysia, 2017)
Salmonella spp. is a pathogenic microbial contaminant in beef of worldwide importance. It has the ability to colonize the gastrointestinal tract of animals without producing any clinical sign. It may lead to infections in human when the contaminated meat was consumed. The main objective of this study was to evaluate the contamination of Salmonella spp. on beef carcasses and meat contact surfaces at selected abattoirs in Selangor, Malaysia. A total of 152 swabs from beef carcasses (n = 104) and meat contact surfaces (n = 48) were collected from the selected abattoirs in October 2015 to June 2016. The collected samples were examined for total viable count and prevalence of Salmonella spp. Salmonella-positive samples were confirmed by routine biochemical tests and Gram staining. The results showed that all samples contained an average viable count of 4.56 ± 1.23 Log CFU/cm2. The overall prevalence of Salmonella spp. was 21.05% which beef carcasses and meat contact surfaces contributed 11.18% and 9.87%, respectively to the overall prevalence. The prevalence of Salmonella spp. on meat contact surfaces was higher than that on beef carcasses could be attributed to poor hygienic practices at the abattoirs. However, despite a lower prevalence of Salmonella spp. on the beef carcasses, beef could still be a potential vehicle for foodborne infections. This study suggests implementation of preventive measures and good hygienic practices at abattoirs in order to avoid cross-contamination on beef prepared for retail markets.